2016
DOI: 10.7554/elife.10786
|View full text |Cite
|
Sign up to set email alerts
|

Non-canonical antagonism of PI3K by the kinase Itpkb delays thymocyte β-selection and renders it Notch-dependent

Abstract: β-selection is the most pivotal event determining αβ T cell fate. Here, surface-expression of a pre-T cell receptor (pre-TCR) induces thymocyte metabolic activation, proliferation, survival and differentiation. Besides the pre-TCR, β-selection also requires co-stimulatory signals from Notch receptors - key cell fate determinants in eukaryotes. Here, we show that this Notch-dependence is established through antagonistic signaling by the pre-TCR/Notch effector, phosphoinositide 3-kinase (PI3K), and by inositol-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…The miRNAs relatively overexpressed in SCCs included miR-994, which has been found to be part of intronic sequence of ΔNp63 and is highly expressed keratinocytes [ 25 ], as well as miR-224, which has been implicated in the progression of colorectal cancer and non-small cell lung cancer (NSCLC) [ 26 , 27 ]. On the contrary, miRNAs upregulated in ADCs included miR-215, which has been shown to modulate gastric tumor cell proliferation by targeting RB1 [ 28 ], and miR-375, which has been observed to be upregulated in lung adenocarcinoma but downregulated in lung squamous cell carcinoma, and promotes cell proliferation by decreasing levels of ITPKB , a putative tumor suppressor [ 29 , 30 ]. Interestingly, also downregulated in ADCs was miR-149, which was demonstrated previously to have tumor suppressor capacity in breast cancer migration and invasion by targeting small GTPases Rap1a and Rap1b [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The miRNAs relatively overexpressed in SCCs included miR-994, which has been found to be part of intronic sequence of ΔNp63 and is highly expressed keratinocytes [ 25 ], as well as miR-224, which has been implicated in the progression of colorectal cancer and non-small cell lung cancer (NSCLC) [ 26 , 27 ]. On the contrary, miRNAs upregulated in ADCs included miR-215, which has been shown to modulate gastric tumor cell proliferation by targeting RB1 [ 28 ], and miR-375, which has been observed to be upregulated in lung adenocarcinoma but downregulated in lung squamous cell carcinoma, and promotes cell proliferation by decreasing levels of ITPKB , a putative tumor suppressor [ 29 , 30 ]. Interestingly, also downregulated in ADCs was miR-149, which was demonstrated previously to have tumor suppressor capacity in breast cancer migration and invasion by targeting small GTPases Rap1a and Rap1b [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, ITPKB was disrupted in 16% of cHL cases by truncating mutations that eliminate its protein kinase domain and, as a consequence, are predicted to blunt its antagonistic activity toward the AKT kinase. 33 Although the function of ITPKB and the pathways that may be modulated by its activity have not been studied in normal GC B cells, ITPKB inactivation may provide a genetic basis to the aberrant PI3K-AKT signaling activity that is known to support HRS cells viability and that is, again, potentially susceptible of pharmacologic inhibition. 34,35 We did not observe any grossly evident enrichment of specific mutated genes in samples analyzed at relapse vs initial diagnosis, with the limitation of the small number of relapsed cases analyzed (n 5 6).…”
Section: Discussionmentioning
confidence: 99%
“…ITPKB encodes for a kinase converting the second messenger inositol trisphosphate (IP3) to IP4, a soluble antagonist of the AKTactivating PI3K-product IP3. 33 All 4 ITPKB-mutated lymphomas showed disruptive frame-shifting variants predicted to generate truncated proteins lacking the kinase domain and, therefore, to boost PI3K-AKT signaling, a characteristic and growth-promoting feature of HRS cells that is amenable to pharmacologic inhibition. 34,35 In addition, 1 of these 4 cases harbored 3 missense mutations in the gene exon 2, the significance of which remains to be established.…”
Section: Frequent Inactivating Mutations Of Itpkb In Chlmentioning
confidence: 99%
“…In CD4 + CD8 + thymocytes, IP 4 promotes PIP 3 binding to the Itk/Tec PH domains to establish a feedback loop of PLCγ1 activation ( 20 , 21 ). In neutrophils, NK cells, CD4 − CD8 − thymocytes undergoing β-selection and in hematopoietic stem cells (HSC), IP 4 competition with PIP 3 or PI(3,4)P 2 for binding to its PH domain may limit Akt membrane recruitment and activation ( 22 27 ). IP 4 can also inhibit RASA3/GAP1 IP4BP -binding to PI(4,5)P 2 or PIP 3 ( 28 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adding a non-canonical perspective to the mechanisms controlling PI3K function, we and others found that PIP 3 activity in hematopoietic cells can also be dampened through antagonism with the soluble PIP 3 -analogs inositol(1,3,4,5)tetrakisphosphate (IP 4 , Figure 1 ) and inositol-heptakisphosphate, also called diphosphoinositol-pentakisphosphate (hereafter IP 7 ) ( 22 27 ). Because IP 4 is identical to the cytoplasm-exposed, PH domain-binding PIP 3 headgroup, IP 4 and PIP 3 can compete for binding to the Akt PH domain.…”
Section: Introductionmentioning
confidence: 99%